Manuscript contexts and the transmission of the Agnus Castus herbal in MS Sloane 3160 - Esteve Ramos, María José (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
MS Sloane 3160 is a miscellaneous volume containing one copy of the herbal Agnus Castus in Middle English. Traditionally, editions focused on texts in isolation and did not look in detail to the rest of the material, diminishing the potential of manuscript contexts in explaining how texts flow and are received by a specific audience. If we consider these groupings of texts a collective product in which all the co-texts are part of an internal dialogue, the importance of looking at the whole volume from a collective perspective becomes paramount in understanding the final aim of the compiler, and the processes of transmission of text and/or texts. The objective of this article has been to study the arrangement of the material contained in MS Sloane 3160 as a starting point to frame future comparison with manuscripts containing the same herbal. The results point to the identification of patterns which would confirm the “anthologistic impulse” (Lerer 2000). The structure of this manuscript would contain a spectrum of the most important areas that would cover the contents of a typical vademecum of the time, including religious texts, but more studies are needed in order to be able to assess these contexts in medical miscellanies. The impact and transmission of the Agnus Castus herbal needs to be studied collectively, and assessing the manuscript contexts in which the text is naturally embedded points to the right direction in understanding all the processes therein. Keywords: miscellanea; Middle English; medical manuscripts; Agnus Castus